Investigation of thermal contaminants in coffee beans induced by roasting: A kinetic modeling approach - Zhu, Mengting; Long, You; Ma, Yingjie; Huang, Yousheng; Wan, Yin; Yu, Qiang; Xie, Jianhua; Chen, Yi (Food chemistry, 2022)
•Kinetics of thermal contaminants in coffee beans during roasting were studied.•Formation and subsequent elimination of AA and 5-HMF followed first-order kinetics.•Increase of furan, methyl furans during roasting described by empirical, logistic models.•Decrease of moisture and increase of weight loss described by first-order kinetics. The roasting-induced formation of thermal contaminants in coffee beans, including 5-hydroxymethylfurfural (5-HMF), acrylamide (AA), furan (F), 2-methyl furan (2-MF), and 3-methyl furan (3-MF), was investigated using a kinetic modeling approach. Results showed that AA and 5-HMF formation and elimination occur simultaneously in coffee beans during roasting and that the related reactions follow first-order reaction kinetics. The concentrations of F, 2-MF, and 3-MF increased throughout the roasting experiment, and variations in the concentrations of these compounds during roasting could be best described by empirical, logistic model. The increase in weight loss and decrease in moisture content of the beans during roasting also displayed first-order reaction kinetics. High coefficients of determination (R2 > 0.981) were observed for all fitted models, and the reaction rate constants of all models followed the Arrhenius law.